HUBUNGAN HUKUM DAN KEADILAN DI TINJAU DARI FILSAFAT HUKUM - Hutabarat, Dany Try Hutama; Hidayat, Yunia Amanda; Amida, Nur; Yusuf, Muhammad; Hazali, Hazali; Rawi, Miftahul Khoiroh; Julianto, April; Sirait, M.Munawir; Julianto, Lafirsto Yogkismun; Affandi, Ikhwan; Nazunda, Nazunda; Aldina, Cindy (Nusantara Hasana Berdikari, 2022)
The law appears as the implication of an essence that offers a resolution to the collectivity of feuds in society, therefore an ideal law is needed to resolve conflicts and disputes. can involve individuals or groups. Basically it is not allowed to deviate from arbitrary actions, justice is the last joint as a legal goal because actually law is moral, meaning that laws and legal norms must be in accordance with moral norms, every law that is implemented there is a demand for justice then law without justice will be in vain so that law is no longer valuable in front of society, combining law and justice is not easy but no matter how difficult it must be done for the sake of the authority of the state and the judiciary because the basic rights of law are rights that belong to the I justice.